Otolith Microchemistry and Demographic History Provide New Insight into the Migratory Behavior and Heterogeneous Genetic Divergence of Coilia grayii in the Pearl River - Gongpei Wang; Qindong Tang; Zhi Chen; Dingli Guo; Lei Zhou; Han Lai; Guifeng Li (Fishes, 2022)
Coilia grayii is the anadromous form of anchovy that is distributed in the East and South China Seas. It is a common fish species in the estuarine area of the Pearl River. Nevertheless, freshwater populations appear upstream in the Pearl River, but the migratory pathway has been mostly impeded by dam construction. Behavioral differences and constrained habitat within tributaries are suspected of promoting genetic divergence in these populations. In this study, we investigated the migratory behavior and genetic divergence of six populations of C. grayii fragmented by dams based on the otolith strontium/calcium (Sr/Ca) ratio, mitochondrial DNA, and microsatellite genotyping. All populations were in freshwater with low Sr/Ca ratios, except the estuarine population (Humen population) hatched in brackish water. Reduced nucleotide diversity corresponding to distance was observed. Populations from distant hydrological regions exhibited a decline in genetic diversity and a significant difference with the remaining populations after fitting the isolation by distance model. Pairwise fixation indices confirmed these results and moderate and significant differentiation was found between Hengxian site and downstream sites. Furthermore, STRUCTURE analyses revealed that all separated populations exhibited an admixed phylogenetic pattern except for individuals from the Hengxian locality. The upstream sites showed significantly increased resistance to gene flow from the estuarine population because of isolation by the dam. The results of the neutrality test and Bayesian skyline plots demonstrated complex demography—individuals’ experienced historical expansion and partial upper-dam populations had recently undergone a colonization, forming a new genetic structure. Accordingly, this study demonstrates differences in the migration pattern and genetic differentiation of C. grayii as a consequence of demographic history and current processes (habitat fragmentation and colonization).